(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Nowadays in globalization period one of important task is forming among rising youth generation the sense of relevancy sense to Motherland. That has to helps to protect them from destructive and strangers ideology, propaganda destroying ideas. The article is devoted to specifics of forming among youth sense of patriotism in the process of globalization. There are discussed as well characteristic features and properties of the youth, especially teenagers on the age of personality forming.